Efeitos dos diferentes tempos de início de treinamento físico após o infarto do miocárdio sobre a função cardíaca e o remodelamento ventricular esquerdo em ratas ovariectomizadas - Claudio, Erick Roberto Gonçalves (2017)
The aim of the present study was to evaluate the effects of the different time of exercise training (ET) initiation after myocardial infarction (MI) on the cardiac function and the ventricular remodeling in ovariectomized rats (OVX). Twelve-week-old OVX female Wistar rats (Rattus Norvegicus Albinus) were randomly divided into four groups: MI-SHAM (SHAM), MI sedentary (MI), MI which started ET 3 days after MI (MI3+ET) and MI which started ET 15 days after MI (MI15+ET). Low to moderate intensity training protocol in a motorized treadmill was performed during 8 weeks (60 min/d, 5 days/wk). Forty-eight hours after the last training session, animals were anesthetized and subject to evaluation of the following parameters: i) Cardiac function after a catheter insertion in the left ventricle (LV); ii) MI area; iii) collagen deposition and myocyte hypertrophy by histology; iv) myocardial oxidative stress by the “in situ” generation of superoxide (DHE) and by the evaluation of the advanced oxidation protein products (AOPP); v) protein expression of type 1 receptor of angiotensin II (AT-1R) and of the membrane isoform of multi-enzymatic complex of NADPH oxidase (gp91phox) by the western blotting (WB) method; vi) antioxidants protein expression, such as superoxide dismutase (SOD-1 and SOD-2) and catalase (CAT), also by WB; vii) antioxidant enzymes activities (SOD and CAT).